Vở bài tập tiếng Việt 2 /. T.2 Nguyễn Minh Thuyết chủ biên, Nguyễn Thị Hạnh, Lê Phương Nga, Trần Hoàng Túy Nguyễn Minh Thuyết chủ biên, Nguyễn Thị Hạnh, Lê Phương Nga, Trần Hoàng Túy / Nguyễn Minh Thuyết chủ biên, Nguyễn Thị Hạnh, Lê Phương Nga, Trần Hoàng Túy - Nguyễn, Minh Thuyết chủ biên
Đầu trang nhan đề:Vở bài tập tiếng Việt 2